PERBEDAAN TINGKAT DEPRESI PADA FASE PRAMENSTRUASI MAHASISWA FAKULTAS KEDOKTERAN DAN FAKULTAS EKONOMI UNIVERSITAS LAMBUNG MANGKURAT - Yasmina, Alfi; Noor, Meitria Syahadatina; Risnawati, Risnawati (Jurnal Publikasi Kesehatan Masyarakat Indonesia, 2014)
Depression may be caused by external factors, such as the pressure of study load, and by internal factors, such as depression in premenstrual phase affected by the decrease in estrogen level. The aim of this research was to find out the difference in depression level in premenstrual phase between Medical Faculty students and Economic Faculty students in Lambung Mangkurat University. It was an analytic survey with cross-sectional approach. Samples were taken by non-probability sampling with purposive sampling technique. The samples were 26 students of Medical Faculty from Basic Medical Education Study Program andÂ  16 students of Economic Faculty from Management Study Program, based on the inclusion criteria. Result showed that there were 22 Medical Faculty students (84.62%) who had mild depression, and there were 9 Economic Faculty students who had mild depression and 4 students (25%) who had moderate depression. Data analysis with Mann Whotney U test showed the o value of 0.196. It was concluded that there were no significant difference in depression level in premenstrual phase between Medical Faculty students and Economic Faculty students.Keywords: depression level, premenstrual phase, study load.